ChemInform Abstract: 2H‐Chromenes Generated by an Iron(III) Complex‐Catalyzed Allylic Cyclization. Issue 36 (September 2015) - Calmus, L.; Corbu, A.; Cossy, J.
Abstract A wide variety of 2H‐chromenes is prepared via FeCl3‐catalyzed allylic cyclization under microwave irradiation.